The Nature of Visual Illusion - Fineman, Mark B. (Dover Publications, 1996)
Keywords: Problems, exercises, etc; Visual perception; Visual perception; dept.psy; faculty_collection

A profile analysis of psychopathology in clusters of depersonalization types - Jacobs, J.R.; Bovasso, G. (Dissociation, 1996)
Five types of depersonalization experiences based on scales developed by Jacobs and Bovasso (1992) were used to cluster subjects into six groups. Four relatively small groups which had regular depersonalization experiences were identified: the Derealized, the Self-negating, the Body-detached, and the Profoundly Depersonalized. The fifth group, the Fleetingly Depersonalized, and the sixth group, the Non-depersonalized, constituted 25% and 50% of the population, respectively. A profile analysis indicated qualitative differences between the six groups in their pathological traits, which fell along a continuum of pathological severity. The results support the validity of a multidimensional depersonalization construct which may clarify some of the contradictions and inconsistencies in the literature on depersonalization. Further, the results may facilitate clinicians' differentiation of their patients along a continuum of pathological severity based on the type and frequency of depersonalization experiences which they report.
Keywords: dept.psy; ⛔ No DOI found

Choice with certain and uncertain reinforcers in an adjusting-delay procedure - Mazur, James E (Journal of the Experimental Analysis of Behavior, 1996)
A discrete-trials adjusting-delay procedure was used to investigate the conditions under which pigeons might show a preference for partial reinforcement over 100% reinforcement, an effect reported in a number of previous experiments. A peck on a red key always led to a delay with red houselights and then food. In each condition, the duration of the red-houselight delay was adjusted to estimate an indifference point. In 100% reinforcement conditions, a peck on a green key always led to a delay with green houselights and then food. In partial-reinforcement conditions, a peck on the green key led either to the green houselights and food or to white houselights and no food. In some phases of the experiment, statistically significant preference for partial reinforcement over 100% reinforcement was found, but this effect was observed in only about half of the pigeons. The effect was largely eliminated when variability in the delay stimulus colors was equated for 50% reinforcement conditions and 100% reinforcement conditions. Idiosyncratic preferences for certain colors or for stimulus variability may be at least partially responsible for the effect.
Keywords: *Appetitive Behavior; *Choice Behavior; *Motivation; Animals; Appetitive Behavior; Choice; Choice Behavior; Color Perception; Columbidae; Conditioned reinforcers; Key peck; Motivation; Pigeons; Reinforcement Schedule; Reinforcement delay; Reinforcement probability; animal; appetite; article; color vision; decision making; dept.psy; motivation; pigeons and doves; reinforcement; ❓ Multiple DOI

Turn-taking in mother-adolescent conversations about sexuality and conflict - Lefkowitz, Eva S; Kahlbaugh, Patricia E; Sigman, Marian (Journal of Youth and Adolescence, 1996)
The current study examined the nature and style of mother-adolescent conversations, how these conversations differ by subject matter and dyadic and individual differences. Thirty-one mother-adolescent dyads (17 boys, 14 girls) with a child between the ages of 11 and 14 had a nonstructured conversation and conversations about conflict and sexuality They also completed questionnaires on beliefs about acquired immunodeficiency syndrome (AIDS). Conversations were measured for turn taking, total number of words, and conversational dominance, as well as nonverbal measures of affiliation, shame, and contempt Conversations about sexuality involved less turn taking, fewer words, and more mother dominance than nonstructured conversations. Conversations about conflicts involved less turn taking but more words than nonstructured conversations Some gender and age differences were found. Move interactive conflict conversations contained higher levels of affiliation, and lower levels of child shame than conversations with fewer turns or higher mother dominance. In addition, children in move interactive dyads possessed a larger percentage of their mother's AIDS knowledge, and worried about AIDS a moderate amount.
Keywords: dept.psy

To forget or not to forget: The effect of probability of test on directed forgetting - Golding, JM; Roper, KL; Hauselt, J (Quarterly Journal of Experimental Psychology Section a-Human Experimental Psychology, 1996)
Two experiments investigated how individuals use explicit memory cues that designate different probabilities of test. As in typical directed forgetting studies, subjects received words explicitly cued as having either a 0% or a 100% chance of being on a subsequent memory test (i.e. forget and remember cues, respectively). In addition, some words were explicitly cued as having the potential to be either forgotten or remembered (i.e. a 50% cue). Recall of 50% words was between that of 0% and 100% words. In addition, the presence of 50% words lowered recall of the 100% words compared to that of a control group that did not receive the 50% words, but received the same number of 100% words. A think-aloud task indicated that these results were due to the 50% words being treated like either 100% or 0% words at encoding. The results are discussed in terms of the effect of different probabilities of test on the strategic processing and representation of information.
Keywords: Adult; Attention; Female; Humans; Male; Mental Recall; Probability Learning; Verbal Learning; adult; article; attention; dept.psy; female; human; learning; male; recall

Past experience, recency, and spontaneous recovery in choice behavior - Mazur, James E (Learning & Behavior, 1996)
Pigeons' responses on two keys were recorded before and after the percentage of reinforcers delivered by each key was changed. In each condition of Experiment 1, the reinforcement percentage for one key was 50% for several sessions, then either 70% or 90% for one, two, or three sessions, and then 50% for another few sessions. At the start of the second and third sessions after a change in reinforcement percentages, choice percentages often exhibited spontaneous recovery-a reversion to the response percentages of earlier sessions. The spontaneous recovery consisted of a shift toward a more extreme response percentage in some cases and toward a less extreme response percentage in other cases, depending on what reinforcement percentages were previously in effect. In Experiment 2, some conditions included a 3-day rest period before a change in reinforcement percentages, and other conditions included no such rest days. Slightly less spontaneous recovery was observed in conditions with the rest periods, suggesting that the influence of prior sessions diminished with the passage of time. The results are consistent with the view that choice behavior at the start of a new session is based on a weighted average of the events of the past several sessions.
Keywords: Animalia; Columba; animal behavior; animal experiment; article; computer simulation; conditioning; decision making; dept.psy; experience; feeding; model; nonhuman; pigeon; reinforcement; reliability

STIR Success Through Individual Recreation: Working with the low-functioning resident with dementia or Alzheimer's disease: - Russen-Rondinone, Tonya; DesRoberts, Anne-Marie M. (American Journal of Alzheimer's Disease, 1996)
STIR, Success Through Individual Recreation is examined to determine the benefits of individualized recreational activities geared towards the lower functioning...
Keywords: dept.psy

Procrastination by pigeons: Preference for larger, more delayed work requirements - Mazur, James E (Journal of the Experimental Analysis of Behavior, 1996)
In three experiments, pigeons chose between alternatives that required the completion of a small ratio schedule early in the trial or a larger ratio schedule later in the trial. Completion of the ratio requirement did not lead to an immediate reinforcer, but simply allowed the events of the trial to continue. In Experiment 1, the ratio requirements interrupted periods in which food was delivered on a variable-time schedule. In Experiments 2 and 3, each ratio requirement was preceded and followed by a delay, and only one reinforcer was delivered, at the end of each trial. Two of the experiments used an adjusting-ratio procedure in which the ratio requirement was increased and decreased over trials so as to estimate an indifference point-a ratio size at which the two alternatives were chosen about equally often. These experiments found clear evidence for `'procrastination”-the choice of a larger but more delayed response requirement. In some cases, subjects chose the more delayed ratio schedule even when it was larger than the more immediate alternative by a factor of four or more. The results suggest that as the delay to the start of a ratio requirement is increased, it has progressively less effect on choice behavior, in much the same way that delaying a positive reinforcer reduces it effect on choice.
Keywords: *Appetitive Behavior; *Conditioning, Operant; *Motivation; *Reinforcement Schedule; Animals; Appetitive Behavior; Attention; Choice; Choice Behavior; Columbidae; Conditioning, Operant; Delay; Inhibition (Psychology); Inhibition, Psychological; Key peck; Motivation; Pigeons; Problem Solving; Procrastination; Ratio schedules; Reinforcement Schedule; animal; appetite; article; attention; decision making; dept.psy; inhibition (psychology); instrumental conditioning; motivation; pigeons and doves; problem solving; reinforcement

The process of answering direction‐giving questions when someone is lost on a university campus: The role of pragmatics - Golding, Jonathan M; Graesser, Arthur C; Hauselt, Jerry (Applied Cognitive Psychology, 1996)
Two experiments investigated how college students answered direction-giving questions when a confederate asked for directions to a destination on a university campus. The experiments applied the QUEST model (Graesser and Franklin, 1990) to direction giving, emphasizing the pragmatic component of the model that focuses on establishing common ground and dealing with the questioner's goals. The two experiments had different articulations of the direction-giving question (i.e.'How do you get to destination X?' versus `Where is destination X?'), and a different destination. The answers generated by subjects supported both aspects of the pragmatic component.
Keywords: dept.psy